Mary Poppins [compact disc] : the supercalifragilistic musical : original live cast recording - Sherman, Richard M., 1928-; Sherman, Robert B.; Stiles, George (Walt Disney Records, 2011)
The musical opened in London in the Prince Edward Theatre on 12/15/04, the 40th anniversary of the film's release. Now you can hear the original cast sing the songs of the beloved show in your own home.